Improvement of mechanical properties and water resistance of bio-based thermal insulation material via silane treatment. (20th April 2022) - Al Abdallah, Hyder; Abu-Jdayil, Basim; Iqbal, Muhammad Z.
Abstract: Buildings, whether commercial or residential, consume a huge proportion of the energy produced globally to maintain livable conditions within their walls. It is estimated that 40% of the energy produced is devoted for buildings, which represents around 30% of global CO2 emissions. Most of buildings are equipped with heat insulation materials to reduce the energy loss and help in maintaining the desired conditions. However, most of these heat insulators are derived from fossil fuel or have environmental and safety concerns. Herein, the effect of two different silane treatments on enhancing the compatibility between date palm wood fibers (DPWF) and polylactic acid (PLA) to produce green biodegradable composites was investigated. The composites were fabricated for the use of heat insulation panels in construction, with filler percentage ranging from 0 to 40 wt%. To the best of our knowledge, this is the first work that examines silane treatment on PLA-wood composites in heat insulation for construction and buildings. The DPWFs were treated with aminopropyl triethoxysilane (APTES) using two different solvents: acetone-water solvent mixture (SA), and ethanol-water solvent mixture (SE). The composites were examined to evaluate the effect of treatments on the physical, thermal, and mechanical properties. Furthermore, the composite structure was characterized by FTIR and SEM techniques. The mechanical properties and water resistance of treated composites showed tremendous improvements compared to untreated composites (PLA-UTDPWF). The 20 wt% composites tensile strength increased from 8.6 MPa for PLA-UTDPWF, to 16.5 and 22.4 MPa for PLA-SA and PLA-SE composites, respectively. Nevertheless, the thermal conductivity slightly increased upon fibers treatment, but remained in a low range of values that are appropriate for heat insulation, varying from 0.085 to 0.105 W / ( m ⋅ K ) . Overall, the SE treatment achieved the best improvements by enhancing preferred features such as the mechanical strength and minimizing undesirable features such as water retention, while maintaining low thermal conductivity. The treatments helped in producing clean and biodegradable heat insulations. Graphical abstract: Image 1 Highlights: PLA-Date Palm wood composites were developed as green thermal insulators. Silane treatment on clean, environmentally friendly heat insulator composites was applied. The treatments significantly improved the mechanical properties of composites. Ethanol-based silane treatments improved the water resistance of composites. The treated composites maintained high thermal insulation properties.